The Effect of Financial Deepening on Economic Growth in Indonesia - Astutik, Yanti; Nugroho, Ris Yuwono Yudo (Signifikan: Jurnal Ilmu Ekonomi, 2024)
Research Originality: This study presents a new interaction between the independent variable financial deepening by adding the inflation control variable as a monetary variable, trade openness and remittances as non-monetary variables, and a dummy variable to see the influence of the pandemic period and not the COVID-19 pandemic period on economic growth.Research Purposes: This research aims to determine the effect of financial deepening on economic growth in Indonesia.Research Methods: This research uses quarterly time series data in Indonesia from 2010-2023 and selects an Error Correction Model (ECM) and Robustness Test model.Empirical Results: Research findings show that financial deepening in the long term and short term has a negative effect on economic growth. This happens because financial deepening in Indonesia is still relatively low, at around 40 percent. The trade openness and remittance variables have a positive effect on economic growth, while the dummy COVID-19 variable in the long term has a negative effect on economic growth.Implications: This study implies that the government needs to improve effective coordination in facing challenges in the financial sector and set targets to encourage financial deepening so that financial inclusion can be achieved.JEL Classification: O10, O44, C32, E31, F13, F24